2018
DOI: 10.1093/rheumatology/kex448
|View full text |Cite|
|
Sign up to set email alerts
|

Bone formation in ankylosing spondylitis during anti-tumour necrosis factor therapy imaged by 18F-fluoride positron emission tomography

Abstract: ObjectivesExcessive bone formation is an important hallmark of AS. Recently it has been demonstrated that axial bony lesions in AS patients can be visualized using 18F-fluoride PET-CT. The aim of this study was to assess whether 18F-fluoride uptake in clinically active AS patients is related to focal bone formation in spine biopsies and is sensitive to change during anti-TNF treatment.MethodsTwelve anti-TNF-naïve AS patients [female 7/12; age 39 years (SD 11); BASDAI 5.5 ± 1.1] were included. 18 F-fluoride PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 36 publications
2
18
1
Order By: Relevance
“…First, in the BM of AS patients, most TNAP-positive cells are of myelocyte/monocyte lineages and MSCs. Although we found a diffuse enhancement of TNAP expression in MSCs of the BM of AS, it was reported that only the BM near cortical bone in AS showed localized enhancement of osteogenesis (58). This discrepancy might be explained by a report stating that the unique microenvironmental niche of BM favored the stemness of MSCs and prevented their spontaneous osteogenesis (59).…”
Section: Methodscontrasting
confidence: 74%
“…First, in the BM of AS patients, most TNAP-positive cells are of myelocyte/monocyte lineages and MSCs. Although we found a diffuse enhancement of TNAP expression in MSCs of the BM of AS, it was reported that only the BM near cortical bone in AS showed localized enhancement of osteogenesis (58). This discrepancy might be explained by a report stating that the unique microenvironmental niche of BM favored the stemness of MSCs and prevented their spontaneous osteogenesis (59).…”
Section: Methodscontrasting
confidence: 74%
“…In a recent study, biopsy procedures were used to collect material from PET-positive lesions in the spine for immunohistochemistry. These PET-positive lesions corresponded to osteoid formation and osteoclasts along with cell infiltrates in areas with both bone and connective tissue, which were largely absent in PET-negative lesions [22]. This study also showed that 18 F-NaF PET/CT may detect changes in bone formation in AS during treatment, as one third of the PET-positive lesions in the spine disappeared after 12 weeks of TNF blocker treatment in their population of 12 patients with AS.…”
Section: Discussionmentioning
confidence: 59%
“…In this latter study, 12 patients had a significant decrease in SUV-AUC values (i.e., SUV corrected for individual integrated whole blood activity concentration) in the sacroiliac and costovertebral joints after treatment with tumor necrosis factor (TNF)α inhibitors. 127 Aiming to further increase the diagnostic accuracy at diagnosis and after treatment of PET/CT, several alternative tracers have been explored, in particular in animal models. For instance, it was demonstrated that 68 Ga-citrate has a Fig.…”
Section: Hybrid Imaging Positron Emission Tomography/computed Tomographymentioning
confidence: 99%